Novos paradigmas na aplicação da medida de segurança: a humanização e inclusão social das pessoas com sofrimento psíquico Em conflito com a lei a partir da realidade do estado do Piauí - Ximenes, Nestor Alcebíades Mendes (2019)
The purpose of the research is to analyze the application of security measures in people with psychological distress in conflict with the law in Brazil, starting from the application of the psychiatric reform in comparison with the democratic criminal law established in the Constitution of the Federative Republic of Brazil. The psychiatric reform, from a humanistic and inclusive perspective, ensures the fulfillment of the fundamental principle of the dignity of the human person and the exercise of fundamental rights and guarantees to those who are in security measure of hospitalization, breaking with the sanctioning model that reflects the mental institution secular practice of segregation and mortification of the individual who suffers from mental illness and, for having practiced an act considered criminal offense, is as much a victim of his illness and of the penal system as the person who was victimized by him. The aim of the study is to provide theoretical and practical elements to the criminal justice system to remove from the penal domain the salutary implamentation of therapeutic measures, with the scope of ensuring, outside the penitentiary system and through inclusive practices, the identification of the human being as a person and the reintegration of the individual into the family and social environment. The research also aims at reorienting the individual as a social agent, offering new perspectives in the psychiatric evaluation by a multidisciplinary team, through a new model of deinstitutionalized "therapeutic measure", as an alternative to the system proposed by the Criminal Code, the Code of Criminal Procedure and the Law of Criminal Execution in Brazil, recovering the curative function to those considered inimputable. This is a qualitative-quantitative research, based on a case study, with the observation of mental health incidents of the investigated public and the results verification of the therapeutic residences project in the State of Piauí, as one of the successful alternatives to the hygienist system and also the violator of the Democratic and Social State of Law, rescuing the individual freedoms and citizenship of these inimitable individuals.